163k views
3 votes
-5 (1-5x) +5 (-8x-2)=-4x-8x need a worked out answer for x plz help me

User Pilcrow
by
5.0k points

1 Answer

2 votes

The work inside parentheses cannot be carried out as shown, so the next approach to consider is multiplying the expressions inside the parentheses by -5 and 5 respectively:

-5 + 25x - 40x - 10 = -4x - 8x (Are you sure it's really "-4x - 8x"?)

Combining the x-terms:

-5 - 15x - 10 = -12x

Combining all like terms: -15 = 3x, so that x = -5 (answer)

User Mark LeMoine
by
5.2k points